(untitled) (CIPEEX, 2025)
Introduction: Olfactory dysfunction (OD) is a frequent manifestation of COVID-19, characterized mainly by anosmia and hyposmia, symptoms that can persist for months after the acute phase of the infection, configuring long COVID. Several studies have investigated clinical, genetic and immunological factors that contribute to the maintenance of this condition, including genetic polymorphisms such as apolipoprotein E (APOE), epigenetic changes, local inflammation and history of substance use. Understanding these mechanisms is essential for clinical management and for identifying patients at increased risk of prolonged sensory and cognitive sequelae. Objective: To evaluate the main mechanisms associated with the persistence of olfactory dysfunction in adult patients with long COVID, considering clinical, genetic, immunological and environmental factors. Methodology: This is an integrative review based on articles published in the last five years, consulting the PubMed, LILACS and BVS databases. The descriptors COVID-19, Smell Disorders and Coronavirus Infections were used. Studies that analyzed olfactory dysfunction in adult patients with long COVID were included, covering clinical, genetic and immunological aspects associated with the persistence of symptoms. Studies that did not address the prolonged phase of the disease or that exclusively analyzed the pediatric population were excluded. Results: Literature analysis demonstrated that persistent OD has a specific epidemiological profile, with younger patients and lower hospitalization rates in the acute phase. The E4 allele of the APOE gene appears to act as a protective factor against prolonged OD. Furthermore, objective assessment of olfactory function through standardized tests was shown to be a predictor of post-COVID conditions associated with cognitive deficits and fatigue, reinforcing the importance of early screening. Local immunological evidence indicates that although classical autoantibodies were not detected, the presence of antibodies against endothelial cells (AECA) suggests cytopathic damage and persistent inflammation in olfactory tissues. Epigenetic and environmental factors also modulate olfactory function, including odor receptor methylation patterns and history of smoking or substance use, increasing susceptibility to prolonged anosmia and hypogeusia, especially in women and older adults. Despite the high prevalence of subjective symptoms, the demand for specialized care is low, highlighting a gap between symptom perception and clinical objectification. Conclusion: The persistence of olfactory dysfunction in long COVID results from a complex interaction between genetic, immunological, epigenetic and environmental factors. Objective assessment of olfactory function and early clinical follow-up are essential to identify patients at greater risk of sensory and cognitive sequelae. Genetic polymorphisms such as APOE E4, local inflammatory factors and history of smoking or substance use constitute central elements in the maintenance of prolonged OD, offering support for therapeutic strategies and prevention of complications in long COVID.